RfaH contributes to maximal colonization and full virulence of hypervirulent Klebsiella pneumoniae - Qiu, Yichuan; Xiang, Li; Yin, Ming; Fang, Chengju; Dai, Xiaoyi; Zhang, Luhua; Li, Ying (Frontiers in Cellular and Infection Microbiology, 2024)
Hypervirulent K. pneumoniae (hvKp) have emerged as clinically important pathogens, posing a serious threat to human health. RfaH, a transcriptional elongation factor, has been regarded as implicated in facilitating the transcription of long virulence operons in certain bacterial species. In K. pneumoniae, RfaH plays a vital role in promoting CPS synthesis and hypermucoviscosity, as well as mediating bacterial fitness during lung infection. In this study, we aim to conduct a systematic investigation of the roles of rfaH in the survival, dissemination, and colonization of hvKp through in vitro and in vivo assays. We found that bacterial cells and colonies displayed capsule -deficient phenotypes subsequent to the deletion of rfaH in K. pneumoniae NTUH-K2044. We confirmed that rfaH is required for the synthesis of capsule and lipopolysaccharide (LPS) by positively regulating the expression of CPS and LPS gene clusters. We found that the ΔrfaH mutant led to a significantly decreased mortality of K. pneumoniae in a mouse intraperitoneal infection model. We further demonstrated that the absence of rfaH was associated with slower bacterial growth under conditions of low nutrition or iron limitation. ΔrfaH displayed reduced survival rates in the presence of human serum. Besides, the engulfment of the ΔrfaH mutant was significantly higher than that of NTUH-K2044 by macrophages in vivo, indicating an indispensable role of RfaH in the phagocytosis resistance of hvKp in mice. Both mouse intranasal and intraperitoneal infection models revealed a higher bacterial clearance rate of ΔrfaH in lungs, livers, and spleens of mice compared to its wild type, suggesting an important role of RfaH in the bacterial survival, dissemination, and colonization of hvKp in vivo. Histopathological results supported that RfaH contributes to the pathogenicity of hvKp in mice. In conclusion, our study demonstrates crucial roles of RfaH in the survival, colonization and full virulence of hvKp, which provides several implications for the development of RfaH as an antibacterial target.